Surgical treatment of the non-complicated gastroesophageal reflux: fundoplication without division of the short gastric vessels - FELIX,Valter Nilton (2002)
Background - There is today a significant greater number of laparoscopic antireflux procedures for the surgical treatment of gastroesophageal reflux disease and there are yet controversies about the necessity of division of the short gastric vessels and full mobilization of the gastric fundus to perform an adequate fundoplication. Aim - To verify the results of the surgical treatment of non-complicated gastroesophageal reflux disease performing Rossetti modification of the Nissen fundoplication. Patients and Methods - Fourteen patients were operated consecutively and prospectively (mean age 44.07 years); all had erosive esophagitis without Barrett's endoscopic signals (grade 3, Savary-Miller) and they were submitted to the Rossetti modification of the Nissen fundoplication. Endoscopy, esophageal manometry and pHmetry were performed before the procedure and around 18 months postoperatively. Results - There was no morbidity, transient dysphagia average was 18.42 days; there was no register of dehiscence or displacement of the fundoplication and only one patient revealed a light esophagitis at postoperative endoscopy; the others presented a normal endoscopic view of the distal esophagus. All noticed a marked improvement of preoperative symptoms. Lower esophageal sphincter pressure changed from 5.82 mm Hg (preoperative mean) to 12 mm Hg (postoperative mean); lower esophageal sphincter relaxing pressure, from 0.38 mm Hg to 5.24 mm Hg and DeMeester score, from 16.75 to 0.8. Conclusion - Rossetti procedure (fundoplication without division of the short gastric vessels) is an effective surgical method to treat gastroesophageal reflux disease.